Powder composition for three-dimensional molded objects, method for producing thermoplastic resin particles, and three-dimensional molded objects and methods for producing the same.

JP7933302B1Active Publication Date: 2026-10-13TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2025573825
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-12-26
Filing Date
2025-12-15
Publication Date
2026-10-13
Estimated Expiration
2045-12-15

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、エラストマーを配合した降温結晶化温度の低いポリアリーレンスルフィド粉末組成物を三次元造形に用いることで、破断伸度、耐衝撃強度が高く、反りのないポリアリーレンスルフィド造形物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933302000008
    Figure 0007933302000008
  • Figure 0007933302000009
    Figure 0007933302000009
  • Figure 0007933302000010
    Figure 0007933302000010
Patent Text Reader

Abstract

A powder composition for three-dimensional molded objects containing thermoplastic resin particles (A), wherein the thermoplastic resin composition constituting the thermoplastic resin particles (A) is a thermoplastic resin composition comprising (a1) 100 parts by weight of polyarylene sulfide resin and (a2) elastomer in an amount of 1 part by weight or more and 40 parts by weight or less, wherein the D50 particle diameter of the powder composition is 10 μm or more and 150 μm or less, and the cooling crystallization temperature of the powder composition is 150°C or more and 220°C or less. By using a polyarylene sulfide powder composition with a low cooling crystallization temperature and containing elastomer in three-dimensional molding, it is possible to provide polyarylene sulfide molded objects with high fracture elongation and impact strength and no warping.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a powder composition suitably used for producing a three-dimensional shaped object by a powder bed fusion bonding method, a method for producing thermoplastic resin particles, a three-dimensional shaped object, and a method for producing the same. In particular, the present invention relates to providing a three-dimensional shaped object that uses polyarylene sulfide as a matrix and has high elongation at break and high impact resistance.

Background Art

[0002] As a technique for producing a three-dimensional shaped object (hereinafter sometimes simply referred to as a shaped object), a powder bed fusion bonding method is known. A shaped object produced by the powder bed fusion bonding method is manufactured by sequentially repeating a thin layer forming step of forming a thin layer of powder, and a cross-sectional shape forming step of selectively melting the formed thin layer to bond resin powder particles and form the cross-sectional shape of the shaped object. Here, as a method for selectively melting the powder, in addition to the selective laser sintering method in which a powder layer is provided and then a laser is selectively irradiated to a position corresponding to the cross section of the object to be shaped, there is a multi-jet fusion method in which an electromagnetic radiation absorber is printed at a position corresponding to the cross section of the object to be shaped or an electromagnetic radiation inhibitor is printed on the non-sintered surface, followed by irradiation with a laser or other energy rays.

[0003] Conventional material powders for powder bed fusion bonding methods have been limited to thermoplastic resins with low melting points such as polyamide 11 and polyamide 12. Therefore, the application of three-dimensional shaped objects produced by the powder bed fusion bonding method has been limited to uses that do not require strength or heat resistance, such as models and shape confirmation during prototyping, making it difficult to expand their use to mounting members. However, in recent years, the range of available material powders has expanded, and super engineering plastics with high strength and high heat resistance, represented by polyarylene sulfide and polyether ketone ketone, have also become usable in the powder bed fusion bonding method, and three-dimensional shaped objects have begun to be applied not only to shape confirmation uses but also to performance prototyping uses and final parts.

[0004] Polyarylene sulfide is a resin with excellent rigidity, heat resistance, chemical resistance, and electrical properties. Therefore, polyarylene sulfide three-dimensional molded objects are used in various electrical, electronic, mechanical, and automotive parts applications. On the other hand, its elongation at break and impact strength are inferior to polyamide, and in applications requiring high toughness, resins with lower heat resistance, such as polyamide 11 and polyamide 12, are still necessary.

[0005] To address these challenges, Patent Document 1 discloses a modified polyarylene sulfide powder. Patent Document 2 discloses the addition of an impact modifier to polyarylene sulfide. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Special Publication No. 2022-530398 [Patent Document 2] Japanese Patent Publication No. 2023-507413 [Overview of the project] [Problems that the invention aims to solve]

[0007] However, the technology described in Patent Document 1 modifies the polyarylene sulfide, raising concerns that the inherent strength and other properties of the polyarylene sulfide may be compromised. The technology described in Patent Document 2 describes a polyarylene sulfide powder with a high crystallization temperature, raising concerns about its handling, such as the occurrence of warping when manufacturing long molded objects.

[0008] Therefore, the present invention aims to provide polyarylene sulfide three-dimensional molded objects that have high fracture elongation, impact strength, and no warping, in order to further expand the applications of polyarylene sulfide three-dimensional molded objects.

[0009] [Means for solving the problem]

[0010] To solve the above problems, the present invention has the following configuration. That is, (1) A powder composition for three-dimensional molded objects comprising thermoplastic resin particles (A), wherein the thermoplastic resin composition constituting the thermoplastic resin particles (A) is a thermoplastic resin composition comprising (a1) 100 parts by weight of polyarylene sulfide resin and (a2) elastomer in a ratio of 1 part by weight to 40 parts by weight, wherein the D50 particle size of the powder composition is 10 μm or more and 150 μm or less, and the cooling crystallization temperature of the powder composition is 150°C or more and 220°C or less. (2) The powder composition according to (1), characterized in that the elastomer (a2) has a reactive functional group. (3) The powder composition according to (1) or (2), characterized in that the glass transition temperature (Tg) of the elastomer (a2) is 0°C or less. (4) The powder composition according to any one of (1) to (3), characterized in that the (a2) elastomer is at least one selected from the group consisting of olefin-based elastomers and silicone-based elastomers. (5) The powder composition according to any one of (1) to (4), characterized in that, in the morphology observed by electron microscope, the thermoplastic resin particles (A) consist of (a1) a polyarylene sulfide resin as the matrix resin and (a2) an elastomer forming an island phase, and the number-average dispersion particle diameter of the island phase is 10 μm or less. (6) The powder composition according to any one of (1) to (5), wherein the D90 / D10 in the particle size distribution of the powder composition is 2 or more and 10 or less. (7) The powder composition according to any one of (1) to (6), wherein the powder composition comprises thermoplastic resin particles (A) and resin particles (B) composed of a resin composition different from the thermoplastic resin composition constituting the thermoplastic resin particles (A), wherein the resin composition constituting the resin particles (B) comprises at least one selected from the group consisting of (a1) polyarylene sulfide resin and (b) polyarylene sulfide resin different from (a1) polyarylene sulfide resin, and the cooling crystallization temperature of the resin particles (B) is 150°C or higher and 220°C or lower. (8) The powder composition according to any one of (1) to (7), characterized in that the total amount of thermoplastic resin particles (A) and resin particles (B) is 100 parts by weight, and the content of thermoplastic resin particles (A) is 1 part by weight or more and 100 parts by weight or less. (9) The powder composition according to any one of (1) to (8), characterized in that the cooling crystallization temperature of the thermoplastic resin particles (A) is 150°C or more and 220°C or less. (10) The powder composition according to any one of (1) to (9), wherein the total amount of thermoplastic resin particles (A) and resin particles (B) composed of a resin composition different from the thermoplastic resin composition constituting the thermoplastic resin particles (A) is 100 parts by weight, and the amount of inorganic reinforcing material (C) is 10 parts by weight or more and 100 parts by weight or less. (11) The powder composition according to any one of (1) to (10), wherein the total of thermoplastic resin particles (A) and resin particles (B) composed of a resin composition different from the thermoplastic resin composition constituting the thermoplastic resin particles (A) is 100 parts by weight, and the powder composition contains 0.1 parts by weight to 10 parts by weight of inorganic fine particles (D) with a particle size of 20 nm to 500 nm. (12) A powder composition according to any one of (1) to (11), wherein when a dumbbell test specimen is prepared by powder bed fusion bonding in accordance with ISO 527-2 (2012) with its longitudinal direction parallel to the direction in which the recoater moves (X direction), the tensile elongation at break of the test specimen in the X direction, measured according to ISO 527-2 (2012), is 1.5% or more. (13) Using a powder bed fusion bonding method, a dumbbell test specimen was prepared in accordance with ISO 527-2 (2012) such that the longitudinal direction was parallel to the direction (X direction) in which the recoater moved. A test specimen was cut from the obtained dumbbell test specimen along the parallel section and measured according to ISO 179 (2010) to obtain a Charpy impact strength (without notch) of 3.5 kJ / m². 2 The above is a powder composition according to any one of (1) to (12). (14) A method for producing thermoplastic resin particles (A) comprising the following steps (1) to (3). (1) A process of melt-mixing (a2) 1 to 40 parts by weight of elastomer with (a1) 100 parts by weight of polyarylene sulfide resin, and then pelletizing. (2) A process of crushing the pellets obtained in process (1). (3) A step in which the particles crushed in step (2) are passed through a filter with a mesh size of 45 μm or more and 250 μm or less. A method for manufacturing a three-dimensional object, comprising supplying a powder composition described in any of (1) to (13) to a powder bed fusion bonding three-dimensional object manufacturing apparatus. (16) A three-dimensional object characterized in that, in the morphology observed by an electron microscope, (a1) a polyarylene sulfide resin is the matrix resin, and (a2) an elastomer forms an island phase, and the number-mean dispersion particle size of the island phase is 10 μm or less. (17) The three-dimensional object according to (16) obtained by a powder bed fusion method using any of the powder compositions described in (1) to (13). [Effects of the Invention]

[0011] According to the present invention, by using a polyarylene sulfide powder composition with a low cooling crystallization temperature and containing an elastomer in three-dimensional fabrication, it is possible to provide polyarylene sulfide fabricated products with high fracture elongation, impact strength, and no warping. [Brief explanation of the drawing]

[0012] [Figure 1]This is a schematic diagram showing an example of a manufacturing apparatus for a three-dimensional shaped object according to the present invention. [Figure 2] This is a transmission electron micrograph of a cross section of the thermoplastic resin particles (A)-1 obtained in Production Example 1. [Figure 3] This is a transmission electron micrograph of a cross section of the three-dimensional shaped object obtained in Example 2. [Modes for Carrying Out the Invention]

[0013] Hereinafter, the present invention will be described in detail along with embodiments. The present invention relates to a powder composition for three-dimensional shaped objects containing thermoplastic resin particles (A), wherein the thermoplastic resin composition constituting the thermoplastic resin particles (A) is a thermoplastic resin composition obtained by blending 1 part by weight or more and 40 parts by weight or less of (a2) an elastomer with respect to 100 parts by weight of (a1) a polyarylene sulfide resin, and the powder composition has a D50 particle diameter of 10 μm or more and 150 μm or less, and a cooling crystallization temperature of 150°C or more and 220°C or less.

[0014] [(a1) Polyarylene Sulfide Resin] The (a1) polyarylene sulfide resin of the present invention is a resin having a repeating unit of the formula: -(Ar-S)- as the main constituent unit.

[0015] Ar is a group containing an aromatic ring whose bond is present on the aromatic ring, and examples thereof include divalent repeating units represented by the following formula (A) to formula (K), among which the repeating unit represented by formula (A) is particularly preferred.

[0016] [Chemical Formula]

[0017] Here, R1 and R2 in the above formula are substituents selected from hydrogen, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, and a halogen group, and R1 and R2 may be the same or different.

[0018] Furthermore, the polyarylene sulfide resin in the present invention may be any of the following: a random copolymer containing the above repeating units, a block copolymer, or a mixture thereof.

[0019] Representative examples of these include polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfide ketone, random copolymers thereof, block copolymers thereof, and mixtures thereof. Particularly preferred polyarylene sulfide resins include polyphenylene sulfide, polyphenylene sulfide sulfone, and polyphenylene sulfide ketone containing 80 mol% or more, particularly 90 mol% or more, of p-phenylene sulfide units as the main constituent units of the polymer.

[0020] [(a2) Elastomer] The (a2) elastomer of the present invention is a polymer compound having rubber elasticity.

[0021] The (a2) elastomer of the present invention preferably contains reactive functional groups, from the viewpoint of improving the fracture elongation and impact strength of the three-dimensional molded object by forming intermolecular bonds with the polyarylene sulfide resin, and from the viewpoint of preventing dragging of the molded object.

[0022] The dragging of the molded object in this invention refers to the phenomenon in which the surface to which resin powder particles are bonded in the layering direction is dragged when layering powder. This phenomenon occurs when a powder composition containing two or more resins with different thermal properties is used as raw material, and the three-dimensional molding conditions are set according to the thermal properties of the resin with high heat resistance, and molding is performed. In detail, the resin with low heat resistance melts during molding, and adheres the surface of the already bonded resin powder particles to the powder during layering, causing the molded object to be dragged as layering progresses. To avoid this phenomenon, it is necessary to prevent the resin with low heat resistance from functioning as an adhesive. To achieve this, the elastomer should not be dry-blended with the polyarylene sulfide resin powder, but rather dispersed within the polyarylene sulfide. Furthermore, when using a thermoplastic elastomer, it is preferable that the thermoplastic elastomer has reactive functional groups that can form intermolecular bonds with the polyarylene sulfide resin so that the thermoplastic elastomer does not bleed out from within the polyarylene sulfide resin. On the other hand, since thermosetting elastomers do not soften when heated, there is little concern about bleed-out even if they do not have reactive functional groups. However, from the viewpoint of improving elongation at break and impact strength, it is preferable to have reactive functional groups.

[0023] The reactive functional groups of the (a2) elastomer of the present invention are not particularly limited, and examples include vinyl groups, epoxy groups, carboxyl groups, acid anhydride groups, ester groups, aldehyde groups, carbonyl dioxy groups, haloformyl groups, alkoxycarbonyl groups, amino groups, hydroxyl groups, styryl groups, methacrylic groups, acrylic groups, ureido groups, mercapto groups, sulfide groups, isocyanate groups, hydrolyzable silyl groups, oxazoline groups, etc., but hydroxyl groups, epoxy groups, carboxyl groups, amino groups, acid anhydride groups, amino groups, hydroxyl groups, isocyanate groups, and oxazoline groups are preferred, and two or more of these reactive functional groups may be included.

[0024] From the viewpoint of improving the fracture elongation and impact strength of the three-dimensional fabricated object, the glass transition temperature Tg of the (a2) elastomer of the present invention is preferably 0°C or lower.

[0025] The preferred upper limit of the glass transition temperature Tg of the (a2) elastomer of the present invention is 0°C or less, more preferably -20°C or less, even more preferably -40°C or less, particularly preferably -60°C or less, significantly preferably -80°C or less, and most preferably -100°C or less.

[0026] Here, the glass transition temperature Tg of the elastomer (a2) of the present invention is defined as the midpoint obtained from the baseline of the baseline shift in the DSC curve detected when differential scanning calorimeter measurement is performed under nitrogen gas flow conditions from -120°C to 50°C at a heating rate of 20°C / min, and the tangent line at the inflection point is obtained.

[0027] Specific examples of the (a2) elastomer of the present invention include thermoplastic elastomers such as olefin-based elastomers, polyester-based elastomers, styrene-based elastomers, and polyamide-based elastomers, and thermosetting elastomers such as silicone-based elastomers. From the viewpoint of improving the elongation at break and impact strength of three-dimensional molded products, olefin-based elastomers and silicone-based elastomers are preferred. From the viewpoint of compatibility with polyarylene sulfide, olefin-based elastomers are more preferred, and from the viewpoint of flame retardancy and chemical resistance, silicone-based elastomers are more preferred. These (a2) elastomers may be formulated not only as a single type, but also in combination of multiple types.

[0028] Examples of olefin-based elastomers include ethylene-butene copolymer, ethylene-propylene copolymer, ethylene-hexene copolymer, ethylene-octene copolymer, ethylene-vinyl acetate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-glycidyl methacrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-styrene copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, ethylene-ethyl acrylate-glycidyl methacrylate copolymer, and ethylene-vinyl acetate-glycidyl methacrylate copolymer. Among these, ethylene-butene copolymer, ethylene-propylene copolymer, ethylene-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, ethylene-ethyl acrylate-glycidyl methacrylate copolymer, and ethylene-vinyl acetate-glycidyl methacrylate copolymer are preferred from the viewpoint of compatibility and dispersibility with polyarylene sulfide resin.

[0029] More specifically, examples include Sumitomo Chemical's "Bondfast" (registered trademark) E (ethylene:glycidyl methacrylate = 88% by weight:12% by weight), "Bondfast" (registered trademark) 2C (ethylene:glycidyl methacrylate = 94% by weight:6% by weight), "Bondfast" (registered trademark) 7L (ethylene:glycidyl methacrylate:methyl acrylate = 70% by weight:3% by weight:27% by weight), "Bondfast" (registered trademark) 7M (ethylene:glycidyl methacrylate:methyl acrylate = 67% by weight:6% by weight:27% by weight), "Bondfast" (registered trademark) CG5001 (ethylene:glycidyl methacrylate = 81% by weight:19% by weight), and Arkema's "LOTADER" (registered trademark) AX8900 (ethylene:glycidyl methacrylate:methyl acrylate = 68% by weight:8% by weight:24% by weight).

[0030] Silicone elastomers have a main chain structure of organopolysiloxane and a molecular structure in which the intermolecules of organopolysiloxane are linked by crosslinking. Preferably, the degree of polymerization of the crosslinked silicone elastomer is 100 or higher, and the weight-average molecular weight is 10,000 or higher. The specific manufacturing method is not particularly limited, but for example, it can be obtained by emulsion curing an organopolysiloxane having at least two terminal active hydrogen functional groups per molecule and an oroganohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms per molecule.

[0031] Silicone elastomers can also be in forms that have copolymer components in part of their molecular structure. Specifically, this includes copolymers of organopolysiloxane components with one or more copolymer components selected from polyolefins (polyethylene, polypropylene, polybutylene, etc.), polycarbonates, polyamides, polybutylene terephthalate, polyester elastomers, polystyrene, polyetherimide, polyketones, liquid crystal polymers, polyetherketones, polyetheretherketones, polyacrylates (polymethyl methacrylate, etc.), etc. However, it is preferable that the silicone elastomer contains 90% or more by weight of constituent units derived from organopolysiloxane.

[0032] The organopolysiloxane structure of the silicone elastomer preferably contains one or more hydrocarbon groups selected from alkyl groups (methyl group, ethyl group, propyl group, butyl group, 2-ethylbutyl group, octyl group, etc.), cycloalkyl groups (cyclohexyl group, cyclopentyl group, etc.), alkenyl groups (vinyl group, propenyl group, butenyl group, heptenyl group, hexenyl group, allyl group, etc.), and aryl groups (phenyl group, tolyl group, xylyl group, naphthyl group, diphenyl group, etc.), with the presence of methyl groups and phenyl groups being particularly preferred.

[0033] Silicone elastomers can take the form of pellets, bulk, powder, powder aggregates, or flakes. From the viewpoint of handling, processability, and dispersibility, pellets, powder, powder aggregates, and flakes are preferred.

[0034] The average primary particle diameter of the silicone elastomer itself is preferably 5 μm or less, more preferably 4 μm or less, even more preferably 3 μm or less, and particularly preferably 1 μm or less, from the viewpoint of dispersibility, flame retardancy, and the toughness of the polyarylene sulfide resin composition. The average primary particle diameter (number-mean particle diameter) of the silicone elastomer itself can be calculated by randomly identifying the diameters of 100 particles from scanning electron microscope images and calculating their arithmetic mean. In the above images, if the particle is not perfectly circular, i.e., elliptical, the maximum diameter of the particle is used as its particle diameter.

[0035] Silicone-based elastomers may also be composites containing organopolysiloxane as a constituent unit. Core-shell rubber (silicone-acrylic core-shell rubber) in which silicone elastomer particles are covered with an acrylic component, or composite powders in which silicone elastomers are covered with silicone resin can also be used. However, from the viewpoint of flame retardancy and long-term durability, it is preferable that the organopolysiloxane content be 90% by weight or more.

[0036] Specifically, examples include Dow Toray's "Dowsil" (registered trademark) EP2600, "Dowsil" (registered trademark) EP2720, and Dow Toray's "Dowsil" (registered trademark) EP5500.

[0037] [Thermoplastic resin particles (A)] The thermoplastic resin particles (A) of the present invention are a thermoplastic resin composition obtained by blending (a2) elastomer in an amount of 1 to 40 parts by weight with (a1) polyarylene sulfide resin.

[0038] (a2) If the amount of elastomer is less than 1 part by weight, the fracture elongation and impact strength of the three-dimensional molded product will not improve. (a2) The lower limit of the amount of elastomer is preferably 1.2 parts by weight or more, and more preferably 1.5 parts by weight or more. (a2) If the amount of elastomer exceeds 40 parts by weight, the mechanical properties inherent to polyarylene sulfide will be impaired. (a2) The upper limit of the amount of elastomer is preferably 35 parts by weight or less, more preferably 30 parts by weight or less, even more preferably 25 parts by weight or less, particularly preferably 20 parts by weight or less, significantly preferably 15 parts by weight or less, and most preferably 10 parts by weight or less.

[0039] Methods for compounding (a2) elastomer with (a1) polyarylene sulfide resin of the present invention include compounding in a molten state and compounding in a solution state, but from the viewpoint of simplicity, compounding in a molten state is preferably used. For compounding in a molten state, melt kneading by an extruder or melt kneading by a kneader can be used, but from the viewpoint of productivity, melt kneading by an extruder that can produce continuously is preferably used. For melt kneading by an extruder, at least one extruder such as a single-screw extruder, twin-screw extruder, quadruple-screw extruder, or twin-screw single-screw composite extruder can be used, but from the viewpoint of kneadability, reactivity and productivity improvement, a twin-screw extruder or quadruple-screw extruder can be preferably used, and melt kneading by a twin-screw extruder is the most preferred.

[0040] (a1) The thermoplastic resin obtained by compounding (a2) an elastomer with polyarylene sulfide resin is preferably pelletized in order to simplify the particle formation process described later.

[0041] A more specific method of melt-kneading is, although not necessarily limited thereto, preferably using a twin-screw extruder with an L / D (L: screw length, D: screw diameter) of 10 or more, preferably 20 or more, and having two or more, preferably three or more kneading sections. There is no particular upper limit to the L / D, but 60 or less is preferable from an economic standpoint. Similarly, there is no particular upper limit to the number of kneading sections, but 10 or less is preferable from a productivity standpoint. The ratio of the kneading section to the total screw length is preferably 5% or more, more preferably 10% or more, and even more preferably 15% or more, from the viewpoint of the dispersibility of (a2) elastomer in (a1) polyarylene sulfide resin. On the other hand, the upper limit of the ratio of the kneading section to the total screw length is preferably 40% or less, from the viewpoint of preventing resin degradation due to excessive shear heat generation during kneading.

[0042] Regarding the screw rotation speed, a mixing method using conditions of 150 to 1000 revolutions / min, preferably 300 to 1000 revolutions / min, and more preferably 350 to 800 revolutions / min is preferred. If the screw rotation speed exceeds 150 revolutions / min, the mixing force is sufficient, so the aggregation of (a2) elastomer is suppressed, leading to the desired elongation at break and impact strength. If the screw rotation speed exceeds 1000 revolutions / min, excessive shear heat generation during mixing causes deterioration of the resin and additives, leading to a decrease in elongation at break, impact strength, and mold fouling, which is undesirable.

[0043] The preferred cylinder temperature range is specifically 280 to 400°C, more preferably 280 to 360°C, and even more preferably 280 to 330°C.

[0044] There are no particular restrictions on the mixing order of the raw materials during melt-mixing, but any method may be used, such as a method in which all raw materials are mixed and then melt-mixed using the method described above, a method in which some raw materials are mixed and then melt-mixed using the method described above, and then the remaining raw materials are mixed in with this mixture and then melt-mixed, or a method in which some raw materials are mixed and then the remaining raw materials are mixed using a side feeder while melt-mixing is performed with a twin-screw extruder.

[0045] The cooling crystallization temperature of the thermoplastic resin particles (A) of the present invention is preferably 150°C or higher and 220°C or lower.

[0046] It is preferable that the cooling crystallization temperature of the thermoplastic resin particles (A) of the present invention is 150°C or higher, as this yields a molded product with high strength. The lower limit of the cooling crystallization temperature of the polyarylene sulfide resin is more preferably 155°C or higher, even more preferably 160°C or higher, and particularly preferably 165°C or higher. Furthermore, it is preferable that the cooling crystallization temperature of the thermoplastic resin particles (A) is 220°C or lower, as this suppresses warping caused by the crystallization of the polyarylene sulfide resin melted by laser irradiation. If warping occurs, it will be dragged when stacking the upper layer, making it impossible to obtain a three-dimensional molded product with the desired shape. The upper limit of the cooling crystallization temperature of the thermoplastic resin particles (A) is more preferably 210°C or lower, even more preferably 205°C or lower, particularly preferably 200°C or lower, significantly preferably 195°C or lower, and most preferably 192°C or lower.

[0047] Here, the cooling crystallization temperature of the thermoplastic resin particles (A) of the present invention, as well as the cooling crystallization temperatures of the resin particles (B), polyarylene sulfide resin, and powder composition described later, were determined by heating the thermoplastic resin particles (A), resin particles (B), polyarylene sulfide resin, and powder composition in a nitrogen atmosphere using a differential scanning calorimeter from 50°C to 340°C at a rate of 20°C / min, holding at 340°C for 5 minutes, and then cooling from 340°C to 50°C at a rate of 20°C / min. The peak with the largest amount of heat generation among the exothermic peaks associated with crystallization was taken as the main peak, and the peak of this peak was taken as the cooling crystallization temperature of the thermoplastic resin particles (A), resin particles (B), polyarylene sulfide resin, and powder composition.

[0048] In the thermoplastic resin particles (A) of the present invention, it is preferable that, in the morphology observed by electron microscopy, (a1) polyarylene sulfide resin is the matrix resin and (a2) elastomer forms island phases.

[0049] (a2) The formation of island phases in the elastomer suppresses the melting and bleeding out of the (a2) elastomer during the manufacturing of three-dimensional objects, and also makes it possible to obtain three-dimensional objects with high fracture elongation and impact strength.

[0050] (a2) The number-average dispersion particle size of the island phase of the elastomer is preferably 10 μm or less, and more preferably 10.0 μm or less.

[0051] When the number-mean-dispersed particle diameter of the island phase is 10 μm or less, the fracture elongation and impact strength of the three-dimensional fabricated object are improved, which is preferable. The number-mean-dispersed particle diameter of the island phase is more preferably 5.0 μm or less, even more preferably 2.0 μm or less, particularly preferably 1.0 μm or less, significantly preferably 0.5 μm or less, and most preferably 0.25 μm or less. There is no particular lower limit to the number-mean-dispersed particle diameter, but from the viewpoint of productivity, it is preferably 0.01 μm or more.

[0052] The number-mean-average particle diameter of the island phase formed by the (a2) elastomer in the thermoplastic resin particle (A) of the present invention is determined by cutting a thin section of 0.1 μm or less from the center of the thermoplastic resin particle (A) in the cross-sectional direction, and then photographing the phase structure with a transmission electron microscope at a magnification of approximately 1000 to 5000 times. Next, the number-mean-average particle diameter of the island phase formed by the (a2) elastomer in any 100 dispersed particles in the photograph is determined using the following formula. The number-mean-average particle diameter of the island phase formed by the (a2) elastomer in the thermoplastic resin composition constituting the three-dimensional molded object described later is determined by cutting a thin section of the three-dimensional molded object in the cross-sectional direction and photographing the phase structure with a transmission electron microscope.

[0053]

number

[0054] In the above formula, Mn is the number-average dispersion particle diameter of the dispersed phase of component (a2), a is the major axis, b is the minor axis, and n is the number of measurements, which is 100.

[0055] [Resin particles B] The powder composition of the present invention may include thermoplastic resin particles (A) and resin particles (B) composed of a resin composition different from the thermoplastic resin composition that constitutes the thermoplastic resin particles (A).

[0056] The resin particles (B) of the present invention are composed of a resin composition different from the thermoplastic resin composition that constitutes the thermoplastic resin particles (A). The resin composition that constitutes the resin particles (B) preferably includes thermoplastic resins such as polyarylene sulfide resin (without elastomer), polyamide resin, polybutyl terephthalate resin, polypropylene resin, and polycarbonate resin, as well as thermosetting resins such as epoxy resin and acrylic resin. From the viewpoint of obtaining molded products without warping, a thermoplastic resin composition is preferred, and it is preferable that it contains (b) polyarylene sulfide resin, which is different from (a1) polyarylene sulfide resin, and it is preferable that it contains (a1) polyarylene sulfide resin. The resin composition that constitutes the resin particles (B) may consist of only one type of resin, or it may be a combination of multiple resins of the same type, or a combination of multiple resins of different types, or it may contain organic or inorganic additives.

[0057] The cooling crystallization temperature of the resin particles (B) of the present invention is preferably 150°C or higher and 220°C or lower.

[0058] By mixing resin particles (B) having a cooling crystallization temperature of 150°C to 220°C into the powder composition, even if the cooling crystallization temperature of the thermoplastic resin particles (A) is not between 150°C and 220°C, the cooling crystallization temperature of the powder composition described later can be adjusted to 150°C to 220°C.

[0059] It is preferable that the cooling crystallization temperature of the resin particles (B) of the present invention is 150°C or higher, as this improves the strength of the three-dimensional molded object. The lower limit of the cooling crystallization temperature of the resin particles (B) is more preferably 155°C or higher, even more preferably 160°C or higher, and particularly preferably 165°C or higher. Furthermore, it is preferable that the cooling crystallization temperature of the resin particles (B) is 220°C or lower, as this suppresses warping due to crystallization of the (b) resin melted by laser irradiation. If warping occurs, it will be dragged when stacking the upper layers, making it impossible to obtain a three-dimensional molded object with the desired shape. The upper limit of the cooling crystallization temperature of the resin particles (B) is more preferably 210°C or lower, even more preferably 205°C or lower, particularly preferably 200°C or lower, significantly preferably 195°C or lower, and most preferably 192°C or lower.

[0060] Here, the cooling crystallization temperature of the resin particles (B) of the present invention can be controlled by adjusting the cooling crystallization temperature of the resin (b). A method for adjusting the cooling crystallization temperature to a desired range when the resin (b) is a polyarylene sulfide resin (without elastomer) is described below. As a method for adjusting the cooling crystallization temperature of a polyarylene sulfide resin (without elastomer) to a desired range, one method is to add an organic acid metal salt or an inorganic acid metal salt to the polymerized polyarylene sulfide resin (without elastomer) and wash it. Such washing is preferably performed after removing residual oligomers and residual salts with hot water washing. Examples of organic acid metal salts or inorganic acid metal salts include, but are not limited to, calcium acetate, magnesium acetate, sodium acetate, potassium acetate, calcium propionate, magnesium propionate, sodium propionate, potassium propionate, calcium hydrochloride, magnesium hydrochloride, sodium hydrochloride, and potassium hydrochloride. The amount of such organic or inorganic metal acid salt added is preferably 0.01 to 5% by weight relative to the polyarylene sulfide resin (without elastomer). When washing the polyarylene sulfide resin (without elastomer), it is preferable to use an aqueous solution of such organic or inorganic metal acid salt, and the washing temperature is preferably 50°C to 90°C. The ratio of polyarylene sulfide resin (without elastomer) to aqueous solution is usually preferably selected as a bath ratio of 10 to 500 g of polyarylene sulfide resin (without elastomer) per liter of aqueous solution.

[0061] In the powder composition of the present invention, it is preferable that the total amount of thermoplastic resin particles (A) and resin particles (B) different from thermoplastic resin particles (A) is 100 parts by weight, and the content of thermoplastic resin particles (A) is 1 part by weight or more and 100 parts by weight or less.

[0062] A content of thermoplastic resin particles (A) of 1 part by weight or more is preferable because it improves the elongation at break and impact strength of the three-dimensional molded object. The lower limit of the content of thermoplastic resin particles (A) is more preferably 2 parts by weight or more, even more preferably 3 parts by weight or more, and particularly preferably 5 parts by weight or more. A content of thermoplastic resin particles (A) of 100 parts by weight or less is preferable because it makes it easier to obtain molded objects without warping. The upper limit of the content of thermoplastic resin particles (A) is more preferably 95 parts by weight or less, and even more preferably 90 parts by weight or less.

[0063] [Powder composition] The D50 particle size of the powder composition of the present invention is 10 μm or more and 150 μm or less.

[0064] If the D50 particle size of the powder composition of the present invention is smaller than 10 μm, powder aggregation occurs, and surface roughness occurs due to the aggregates, resulting in the inability to manufacture a homogeneous three-dimensional object, and thus a three-dimensional object with high fracture elongation and impact strength cannot be obtained. The lower limit of the D50 particle size is preferably 15 μm or more, more preferably 20 μm or more, even more preferably 25 μm or more, and particularly preferably 30 μm or more. If the D50 particle size is larger than 150 μm, surface roughness occurs due to coarse particles, resulting in the inability to manufacture a homogeneous three-dimensional object, and thus a three-dimensional object with high fracture elongation and impact strength cannot be obtained. The upper limit of the D50 particle size is preferably 120 μm or less, more preferably 100 μm or less, even more preferably 90 μm or less, and particularly preferably 80 μm or less.

[0065] Here, the D50 particle size of the powder composition of the present invention is the particle size at which the cumulative frequency from the smallest particle size side of the particle size distribution, as measured by a laser diffraction particle size distribution analyzer based on Mie's scattering and diffraction theory, reaches 50%. The D10 particle size of the powder composition of the present invention is the particle size at which the cumulative frequency reaches 10%, and the D90 particle size of the powder composition of the present invention is the particle size at which the cumulative frequency reaches 90%.

[0066] The particle size distribution of the powder composition of the present invention is preferably uniform, and the D90 / D10 ratio in the particle size distribution of the powder composition is preferably between 2 and 10.

[0067] A D90 / D10 of 10 or less is preferable because it allows for the formation of a uniform powder surface and the manufacture of a homogeneous three-dimensional object, thereby obtaining a three-dimensional object with high fracture elongation and impact strength. The upper limit of D90 / D10 is more preferably 8 or less, even more preferably 6 or less, particularly preferably 4 or less, and significantly preferably 3 or less. A D90 / D10 of 2 or more is preferable because it increases the density of the three-dimensional object, improving the fracture elongation and impact strength of the three-dimensional object. The lower limit of D90 / D10 is more preferably 2.2 or more, and even more preferably 2.5 or more.

[0068] The cooling crystallization temperature of the powder composition of the present invention is 150°C or higher and 220°C or lower.

[0069] If the cooling crystallization temperature of the powder composition of the present invention is less than 150°C, a molded object with high strength cannot be obtained. The lower limit of the cooling crystallization temperature of the powder composition is preferably 155°C or higher, more preferably 160°C or higher, and even more preferably 165°C or higher. Furthermore, if the cooling crystallization temperature of the powder composition exceeds 220°C, warping occurs due to the crystallization of the polyarylene sulfide resin melted by laser irradiation. When warping occurs, it drags when stacking the upper layer, making it impossible to obtain a three-dimensional molded object with the desired shape. The upper limit of the cooling crystallization temperature of the powder composition is preferably 210°C or lower, more preferably 205°C or lower, even more preferably 200°C or lower, particularly preferably 195°C or lower, and significantly preferably 192°C or lower.

[0070] The powder composition of the present invention may contain an inorganic reinforcing material (C) to improve its mechanical properties.

[0071] The size of the inorganic reinforcing material (C) used in this invention is not particularly limited, but materials with a maximum dimension of 1 μm or more and 400 μm or less can be used. A maximum dimension of 1 μm or more is preferable because it can further improve the mechanical properties of the three-dimensional molded object. The lower limit of the maximum dimension is more preferably 20 μm or more, and more preferably 50 μm or more. Furthermore, a maximum dimension of 400 μm or less is preferable because it improves the fluidity of the powder composition, and the upper limit of the maximum dimension is more preferably 200 μm or less, and even more preferably 170 μm or less.

[0072] Here, the maximum dimension is the average value obtained by observing the inorganic reinforcement material (C) using an electron microscope, randomly selecting 100 inorganic reinforcement material (C) from images magnified between 10,000 and 100,000 times, and measuring the length at which the distance between two points on the outer contour line of each inorganic reinforcement material (C) is maximized.

[0073] When the inorganic reinforcing material (C) is fibrous, the fiber diameter is preferably 0.1 μm or more and 50 μm or less. A more preferable lower limit for the fiber diameter is 0.5 μm, and particularly preferable is 1 μm. A more preferable upper limit for the fiber diameter is 40 μm, and particularly preferable is 30 μm.

[0074] Examples of the inorganic reinforcing material (C) of the present invention include talc, silica-containing compounds, minerals, glass fibers, glass beads, glass flakes, foamed glass beads, single-crystal potassium titanate, carbon fibers, carbon nanotubes, carbon black, anthracite powder, titanium oxide, magnesium oxide, potassium titanate, mica, asbestos, calcium sulfite, calcium silicate, molybdenum sulfide, boron fibers, silicon carbide fibers, etc., but carbon fibers, glass fibers, and glass beads are preferred. These inorganic reinforcing materials can be used individually or in combination of two or more types.

[0075] The lower the volume resistivity of the carbon fibers used in this invention, the less likely it is that the fibers will aggregate due to static charge when mixed as a powder mixture. Preferably, the volume resistivity is 20 × 10⁻⁴ Ω·cm or less. Here, volume resistivity is the value obtained by measuring the electrical resistance of a bundle of carbon fibers cut from roving and using the following formula. Volume resistivity = Resistivity (Ω) × Carbon fiber bundle width (mm) × Carbon fiber bundle thickness (mm) × Carbon fiber bundle length (mm)

[0076] The powder composition of the present invention preferably contains 10 to 100 parts by weight of an inorganic reinforcing material (C), with a total of 100 parts by weight of thermoplastic resin particles (A) and resin particles other than thermoplastic resin particles (B).

[0077] A content of 10 parts by weight or more of inorganic reinforcing material (C) is preferable because it improves the impact strength of the three-dimensional molded object. The lower limit of the inorganic reinforcing material (C) content is more preferably 15 parts by weight or more, even more preferably 25 parts by weight or more, particularly preferably 30 parts by weight or more, and significantly preferably 35 parts by weight or more. A content of 100 parts by weight or less of inorganic reinforcing material (C) is preferable because it improves the elongation at break of the three-dimensional molded object. The upper limit of the inorganic reinforcing material (C) content is more preferably 80 parts by weight or less, even more preferably 70 parts by weight or less, and particularly preferably 60 parts by weight or less.

[0078] The powder composition of the present invention may contain inorganic fine particles (D) to improve fluidity.

[0079] In the present invention, inorganic fine particles (D) can be added to further improve the fluidity of the powder composition. The fluidity of a powder composition deteriorates due to interactions with neighboring particles when the size of thermoplastic resin particles is small, but by adding inorganic fine particles (D) which have a smaller particle size than thermoplastic resin particles, the interparticle distance can be increased, and the fluidity of the powder composition tends to be improved.

[0080] In the present invention, the D50 particle size of the inorganic fine particles (D) is preferably 20 nm or more and 500 nm or less.

[0081] When the D50 particle diameter of the inorganic fine particles (D) of the present invention is 20 nm or larger, aggregation of the inorganic fine particles (D) is suppressed, a uniform powder surface can be formed, and a homogeneous three-dimensional object can be manufactured, thus making it preferable to obtain a three-dimensional object with high fracture elongation and impact strength. The lower limit of the D50 particle diameter of the inorganic fine particles (D) is more preferably 30 nm or larger, even more preferably 40 nm or larger, and particularly preferably 50 nm or larger. When the D50 particle diameter of the inorganic fine particles (D) is 500 nm or smaller, the fluidity of the powder composition is improved, a uniform powder surface can be formed, and a homogeneous three-dimensional object can be manufactured, thus making it preferable to obtain a three-dimensional object with high fracture elongation and impact strength. The upper limit of the D50 particle diameter of the inorganic fine particles (D) is more preferably 400 nm or smaller, even more preferably 300 nm or smaller, particularly preferably 250 nm or smaller, and significantly preferably 200 nm or smaller. Here, the D50 particle size is a value measured in the same manner as the D50 particle size of the powder composition described above.

[0082] Examples of the inorganic fine particles (D) of the present invention include calcium carbonate particles, silica (silicon dioxide) fine particles, fused silica particles, crystalline silica particles, alumina (aluminum oxide) particles, alumina-containing compound particles, and aluminum particles. Silica fine particles are preferred, and among these, amorphous silica particles, which have low toxicity to the human body, are industrially extremely preferred.

[0083] The shape of the inorganic fine particles (D) can be spherical, porous, hollow, or irregular, and the shape of the inorganic fine particles (D) in this invention is not particularly limited, but a spherical shape is preferred because it exhibits good fluidity.

[0084] The powder composition of the present invention preferably contains 0.1 to 10 parts by weight of inorganic fine particles (D), with a total of 100 parts by weight of thermoplastic resin particles (A) and resin particles other than thermoplastic resin particles (B).

[0085] The inclusion of 0.1 parts by weight or more of the inorganic fine particles (D) of the present invention is preferable because it improves the fluidity of the powder composition and allows for the formation of a uniform powder surface, thereby enabling the manufacture of homogeneous three-dimensional molded objects and improving the elongation at break and impact strength of the three-dimensional molded objects. The lower limit of the inorganic fine particles (D) content is more preferably 0.2 parts by weight or more, and even more preferably 0.3 parts by weight or more. Since including more than 10 parts by weight of inorganic fine particles (D) may cause sintering defects and reduce the elongation at break and impact strength of the three-dimensional molded objects, the upper limit of the inorganic fine particles (D) content is more preferably 6 parts by weight or less, and even more preferably 2 parts by weight or less.

[0086] In the powder composition of the present invention, both the inorganic reinforcing material (C) and the inorganic fine particles (D) described above may be included in amounts within the preferred range described above.

[0087] The inorganic reinforcing material (C) and inorganic fine particles (D) of the present invention are preferably dry-blended in order to improve fluidity.

[0088] Furthermore, the powder composition of the present invention may contain other additives. Examples of other additives include antioxidants, heat stabilizers, weathering agents, lubricants, pigments, dyes, plasticizers, antistatic agents, flame retardants, carbon black, and titanium dioxide, which improve the stability of the powder composition.

[0089] The tensile elongation at break in the X direction of a dumbbell test specimen prepared using the powder composition of the present invention as a raw material by a powder bed fusion bonding method, measured according to ISO 527-2 (2012), is preferably 1.5% or more. Note that the direction in which the recoater moves is defined as the X direction, as will be described later.

[0090] A tensile elongation at break in the X direction of 1.5% or more is preferable because it indicates high elongation at break, expanding the range of applications for the resulting three-dimensional object. A tensile elongation at break in the X direction of 1.6% or more is more preferable, 1.7% or more is even more preferable, and 1.8% or more is particularly preferable.

[0091] The tensile elongation at break in this invention was measured using a Tensilon universal testing machine RTG-1250 (manufactured by A&D Co., Ltd.).

[0092] The Charpy impact strength (without notches) in the X direction of a test specimen cut from a dumbbell test piece prepared by a powder bed fusion bonding method using the powder composition of the present invention, in accordance with ISO 527-2 (2012), was measured according to ISO 179 (2010) and was 3.5 kJ / m². 2 It is preferable that the above conditions are met.

[0093] The Charpy impact strength (without notches) is 3.5 kJ / m². 2 The above specifications result in high impact resistance, which is desirable as it expands the range of applications for the resulting three-dimensionally molded objects. The Charpy impact strength (without notches) is 4.0 kJ / m 2 The above is more preferable, 4.2 kJ / m 2 The above is even more preferable.

[0094] The Charpy impact strength (without notch) in this invention was measured using a digital impact tester DG-UB (manufactured by Toyo Seiki Seisakusho Co., Ltd.).

[0095] [Method for manufacturing thermoplastic resin particles] The method for producing thermoplastic resin particles of the present invention is not particularly limited. Particles obtained by polymerization can be used as thermoplastic resin particles, or particles can be obtained from resins that have been made into pellets, fibers, or films. Furthermore, depending on the form of the thermoplastic resin particles used, the pulverization treatment described below can be performed. Other methods include a spray-drying method after dissolving the raw materials in a solvent, a poor-solvent precipitation method in which an emulsion is formed in a solvent and then brought into contact with a poor solvent, a liquid-drying method in which an emulsion is formed in a solvent and then the organic solvent is dried off, and a forced-melt kneading method in which a sea-island structure is formed by mechanically kneading the resin component to be particleized with a different resin component, and then the sea component is removed with a solvent. Among these, pulverization is preferably used from the viewpoint of economy. There are no particular limitations on the pulverization method, and examples include disc mills, jet mills, bead mills, hammer mills, ball mills, sand mills, turbo mills, and cryogenic grinding. Preferably, dry grinding such as turbo mills, jet mills, and cryogenic grinding is used, and more preferably, cryogenic grinding is used.

[0096] After the production of thermoplastic resin particles, coarse and fine particles can be removed by known methods to adjust them to the desired particle size and particle size distribution. For example, methods such as physical removal using a specified filter, airflow classification separating particles while applying compressed air during weeding, and separation by buoyancy difference in a liquid phase can be used. However, from the viewpoint of separation accuracy, a method of passing the particles through a filter with a specified mesh size is preferred.

[0097] The mesh size of the filter is preferably 45 μm or more and 250 μm or less. A mesh size of 45 μm or more is preferable because it improves the productivity of classification by the filter. A mesh size of 60 μm or more is more preferable. A mesh size of 250 μm or less is preferable because it allows adjustment to the desired D50 particle size and particle size distribution. A mesh size of 200 μm or less is more preferable, 180 μm or less is even more preferable, 125 μm or less is particularly preferable, and 90 μm or less is extremely preferable.

[0098] [Method for manufacturing three-dimensional objects] The method for manufacturing a three-dimensional object according to the present invention involves supplying the above-described powder composition to a three-dimensional object manufacturing apparatus.

[0099] The powder bed fusion method is preferred as the fabrication method for the three-dimensional object of the present invention. The powder bed fusion method is a manufacturing method in which a three-dimensional object is obtained by repeatedly forming a layer of powder composition, melting and welding the position corresponding to the cross-section of the desired object using a heat source such as a laser, and then forming another layer of powder composition on top of it. Details of this method are illustrated with Figure 1.

[0100] (a) In step (a), the stage 2 of the tank 1 in which the molded object is formed is lowered.

[0101] (b) In step (b), the stage 4 of the tank 3 (hereinafter sometimes referred to as the supply tank), which is pre-filled with the powder composition P to be supplied to the tank 1 for forming the molded object, is raised to a height that allows for the supply of a sufficient amount of powder composition P to fill the tank 1 to a predetermined stacking height. Then, the recoater 5 is moved from the left end of the supply tank 3 in the diagram to the right end of the tank 1, and the powder composition P is stacked in the tank 1. The direction parallel to the movement of the recoater 5 is the X direction, and the direction perpendicular to the direction of movement of the recoater 5 on the powder surface of the powder composition P is the Y direction. Reference numeral 7 indicates the coordinate system representing the X, Y, and Z directions. Reference numeral 8 indicates the surface direction in which the powder composition P is stacked, and reference numeral 9 indicates the height direction in which the powder composition P is stacked.

[0102] (c) In step (b), the powder composition P, which was filled into the tank 1 to a predetermined stacking height in step (b), is given meltable thermal energy 6 to selectively melt and sinter according to the molding data.

[0103] In the powder bed fusion method, a three-dimensional object 10 can be obtained by repeatedly performing steps (a) to (c) described above.

[0104] Furthermore, the powder composition supplied to the powder bed fusion three-dimensional manufacturing apparatus can be recovered as appropriate and, for example, regenerated by melting and pulverizing it, or it can be processed to remove molten resin other than the powder composition using a sieve with a mesh size of 1 mm and then supplied to the three-dimensional manufacturing apparatus again, either as is or mixed with unused powder composition.

[0105] Powder bed fusion is further classified into selective laser sintering and multi-jet fusion depending on how thermal energy 6 is applied to the powder composition in step (c). Selective laser sintering is a method in which a laser is irradiated to a shape corresponding to the cross-sectional shape of the object to be fabricated, thereby bonding the powder composition. Multi-jet fusion is a method in which an energy absorption accelerator is applied to a shape corresponding to the cross-sectional shape of the object to be fabricated, or an energy absorption inhibitor is applied to the non-sintered surface, and the resin powder is bonded using electromagnetic radiation.

[0106] The laser light used in selective laser sintering is not particularly limited as long as it does not impair the quality of the polymer particles or polymer particle composition or the fabricated object. Examples include carbon dioxide lasers, YAG lasers, excimer lasers, He-Cd lasers, and semiconductor-pumped solid-state lasers. Among these, carbon dioxide lasers are preferred because they are easy to operate and control.

[0107] Furthermore, while any electromagnetic radiation can be used in the multi-jet fusion method as long as it does not impair the quality of the powder composition or the fabricated object, infrared radiation is preferred because it is relatively inexpensive and provides energy suitable for fabrication. Also, the electromagnetic radiation may or may not be coherent.

[0108] Energy absorption enhancers are substances that absorb electromagnetic radiation. Examples of such substances include carbon black, carbon fibers, copper hydroxyphosphate, near-infrared absorbing dyes, near-infrared absorbing pigments, metal nanoparticles, polythiophene, poly(p-phenylene sulfide), polyaniline, poly(pyrrole), polyacetylene, poly(p-phenylene vinylene), polyparaphenylene, poly(styrene sulfonate), poly(3,4-ethylenedioxythiophene)-poly(styrenephosphonate)p-diethylaminobenzaldehyde diphenylhydrazone, or conjugated polymers consisting of combinations thereof. These may be used individually or in combination.

[0109] Energy absorption inhibitors are substances that do not readily absorb electromagnetic radiation. Examples of such substances include materials that reflect electromagnetic radiation, such as titanium, heat-insulating powders such as mica powder and ceramic powder, and water. These can be used individually or in combination.

[0110] These selective absorbers or selective inhibitors may be used individually or in combination.

[0111] In the process of printing a selective absorbent or selective inhibitor in a shape corresponding to the cross-sectional shape of the object to be fabricated, known methods such as inkjet printing can be used. In this case, the selective absorbent or selective inhibitor may be used as is, or it may be dispersed or dissolved in a solvent before use.

[0112] [Three-dimensional object] In the three-dimensional molded object of the present invention, the thermoplastic resin composition constituting the three-dimensional molded object has, in the morphology observed by electron microscopy, a polyarylene sulfide resin (a1) as the matrix resin and (a2) elastomer forming island phases, and the number-average dispersion particle diameter of the island phases is 10 μm or less, preferably 10.0 μm or less.

[0113] When the number-mean-dispersed particle size of the island phase is 10 μm or less, the fracture elongation and impact strength of the three-dimensional fabricated object are improved. The upper limit of the number-mean-dispersed particle size of the island phase is preferably 5.0 μm or less, more preferably 2.0 μm or less, even more preferably 1.0 μm or less, particularly preferably 0.5 μm or less, and significantly preferably 0.25 μm or less. There is no particular lower limit to the number-mean-dispersed particle size, but from the viewpoint of productivity, it is preferably 0.01 μm or more.

[0114] The number-mean dispersion particle diameter of the island phase formed by (a2) elastomer in the thermoplastic resin composition constituting the three-dimensional object is determined by cutting a thin section of 0.1 μm or less from the center of the three-dimensional object in the cross-sectional direction, and then photographing the phase structure with a transmission electron microscope at a magnification of approximately 1000 to 5000 times. Subsequently, the number-mean dispersion particle diameter is calculated from the major and minor axes of any 100 dispersed particles derived from (a2) elastomer in the photograph using the following formula.

[0115]

number

[0116] In the above formula, Mn is the number-average dispersion particle diameter of the dispersed phase of component (a2), a is the major axis, b is the minor axis, and n is the number of measurements, which is 100. [Examples]

[0117] The present invention will be described below based on examples, but the present invention is not limited to these examples.

[0118] (1) Method for measuring the cooling crystallization temperature of polyarylene sulfide resin, thermoplastic resin particles (A), resin particles (B), powder composition, or three-dimensional molded object. Using a differential scanning calorimeter (DSCQ20) manufactured by TA Instruments, 10 mg of polyarylene sulfide resin, thermoplastic resin particles (A), resin particles (B), powder composition, or three-dimensional molded object was measured under the following conditions in a nitrogen atmosphere. • Hold at 50°C for 1 minute • Heats from 50°C to 340°C, heating rate 20°C / min • Hold at 340°C for 5 minutes • Cooling from 340°C to 50°C, cooling rate 20°C / min

[0119] Among the exothermic peaks associated with crystallization during cooling, the peak with the largest amount of heat generation was designated as the main peak, and its peak was defined as the cooling crystallization temperature for polyarylene sulfide resin, thermoplastic resin particles (A), resin particles (B), powder composition, or three-dimensional molded object.

[0120] (2) Method for measuring D50 particle size and D90 / D10 of powder composition The particle size distribution was measured using a laser diffraction particle size distribution analyzer (Microtrac MT3300EXII) manufactured by Nikkiso Co., Ltd., with a 0.5 wt% aqueous solution of polyoxyethylene cumylphenyl ether (trade name Nonal 912A, manufactured by Toho Chemical Industry Co., Ltd., hereafter referred to as Nonal 912A) as the dispersion medium. Specifically, the cumulative curve was determined by analyzing the scattered light of the laser using the Microtrac method, with the total volume of the fine particles set to 100%. The particle size at the point where the cumulative curve from the small particle size side reaches 10% was defined as D10, the particle size at the point where it reaches 50% was defined as D50, and the particle size at the point where it reaches 90% was defined as D90.

[0121] (3) Tensile elongation at fracture of three-dimensional molded objects The tensile strength at fracture of the three-dimensionally fabricated object was measured using a Tensilon universal testing machine RTG-1250 (manufactured by A&D Corporation) in accordance with ISO 527-2 (2012), after preparing ISO 1A type test specimens using a powder sintering 3D printer.

[0122] (4) Charpy impact strength of three-dimensional objects (without notches) The Charpy impact strength (without notches) of three-dimensionally fabricated objects was evaluated using a digital impact tester DG-UB (manufactured by Toyo Seiki Seisakusho Co., Ltd.) in accordance with ISO 179 (2010), with test specimens obtained by cutting ISO 1A type test specimens fabricated using a powder sintering 3D printer.

[0123] (5) Thermoplastic resin particles (A), number-average dispersion particle diameter of the dispersed phase of component (a2) in the three-dimensional molded object After cutting a thin section of 0.1 μm or less from the center of a thermoplastic resin particle (A) or a three-dimensional object in the cross-sectional direction, the phase structure was photographed using a transmission electron microscope at a magnification of approximately 1000 to 5000 times. Next, the number-mean dispersion particle diameter was determined from the major and minor axes of 100 arbitrary dispersion particles originating from component (a2) in the photographed image using the following formula.

[0124]

number

[0125] In the above formula, Mn is the number-average dispersion particle diameter of the dispersed phase of component (a2), a is the major axis, b is the minor axis, and n is the number of measurements, which is 100.

[0126] [Synthesis Example 1] Synthesis of Polyarylene Sulfide Resin (I) In a 1-liter autoclave equipped with a stirrer, charge 1.00 mole of 47 wt% sodium hydroxide, 1.05 moles of 46 wt% sodium hydroxide, 1.65 moles of N-methyl-2-pyrrolidone (NMP), 0.45 moles of sodium acetate, and 5.55 moles of deionized water, and keep them running. The mixture was gradually heated to 225°C over approximately 2 hours while nitrogen was passed through under pressure. After distilling off 11.70 moles of water and 0.02 moles of NMP, the reaction vessel was cooled to 160°C. The amount of hydrogen sulfide released was 0.01 moles.

[0127] Next, 1.02 moles of p-dichlorobenzene (p-DCB) and 1.32 moles of NMP were added, and the reaction vessel was sealed under nitrogen gas. Then, while stirring at 400 rpm, the temperature was raised in two stages: from 200°C to 240°C in 90 minutes, and from 240°C to 270°C in 30 minutes. Ten minutes after reaching 270°C, 0.75 moles of water were injected into the system over 15 minutes. After 120 minutes at 270°C, the mixture was cooled to 200°C at a rate of 1.0°C / min, and then rapidly cooled to near room temperature to remove the contents.

[0128] The contents were removed, diluted with 0.5 liters of NMP, and the solvent and solids were filtered off using an 80-mesh sieve. The resulting particles were washed several times with 1 liter of warm water, then washed with 800 g of a 0.55 wt% aqueous acetic acid solution, and further washed with 1 liter of warm water. The mixture was then filtered to obtain a cake. The obtained cake was dried under a nitrogen stream at 120°C to obtain polyarylene sulfide resin (I). The cooling crystallization temperature of the obtained polyarylene sulfide resin (I) was 231°C.

[0129] [Synthesis Example 2] Synthesis of Polyarylene Sulfide Resin (II) Polyarylene sulfide resin was obtained in the same manner as in Synthesis Example 1, except that 800 g of 0.45 wt% calcium acetate monohydrate was added to the polyarylene sulfide resin instead of an aqueous acetic acid solution. The cooling crystallization temperature of the obtained polyarylene sulfide resin (II) was 168°C. The cooling crystallization temperatures for Synthesis Examples 1 and 2 are summarized in Table 1.

[0130] [Table 1]

[0131] [Manufacturing Examples 1-4] The elastomers used in the manufacturing example are shown below. (a2)-1 Olefin-based elastomer Ethylene-glycidyl methacrylate-methyl acrylate copolymer (Sumitomo Chemical's "BondFirst" (registered trademark) 7M, ethylene:glycidyl methacrylate:methyl acrylate = 67% by weight:6% by mass:27% by mass) (a2)-2 Silicone-based elastomers Silicone rubber (Dow Toray Industries, Ltd. "Dowsil" (registered trademark) EP5500, polyorganosiloxane content: approximately 90% or more, average primary particle size: 3 μm)

[0132] The compatibilizers used in the manufacturing example are shown below. (a3)-1 Silane coupling agent 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (KBM-303, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0133] The polyarylene sulfide resin obtained in the synthesis example, (a2) elastomer, and (a3) ​​compatibilizer were dry-blended in the proportions shown in Table 2, and then fed into a Japan Steel Works Ltd. TEX30α twin-screw extruder (L / D=30, 2 kneading sections) for melt-kneading. The kneading conditions were 300°C and 300 rpm. After pelletizing with a strand cutter, the mixture was dried at 130°C for 3 hours. The resulting pellets were freeze-milled for 120 minutes and then passed through a sieve with a mesh size of 125 μm to obtain thermoplastic resin particles (A) ((A)-1 to (A)-4). The properties of the obtained particles are shown in Table 2. Figure 2 shows a transmission electron microscope image of the cross-section of thermoplastic resin particle (A)-1 obtained in Production Example 1.

[0134] [Manufacturing Example 5] Manufacturing of resin particles (B) The polyarylene sulfide resin obtained in Synthesis Example 2 was pulverized by freeze-drying for 120 minutes to obtain resin particles (B) with a cooling crystallization temperature of 168°C. The properties of the obtained particles are shown in Table 2.

[0135] [Table 2]

[0136] The inorganic fine particles prepared in the example are shown below. (D)-1 Inorganic fine particles Trimethylsilylated amorphous silica (Shin-Etsu Chemical Co., Ltd. X-24-9500)

[0137] [Examples 1-6, Comparative Example 1] Thermoplastic resin particles (A), resin particles (B), and inorganic fine particles (D) were dry-blended in the proportions shown in Table 3 to obtain a powder composition. This powder composition was then used to fabricate a three-dimensional object using a powder sintering 3D printer (Rafael II 300C-HT, manufactured by Aspect). The properties of the obtained powder composition and the three-dimensional object are shown in Table 3. Figure 3 shows a transmission electron microscope image of the cross-section of the three-dimensional object obtained in Example 2.

[0138] [Comparative Example 2] Thermoplastic resin particles (A) and resin particles (B) were dry-blended in the proportions shown in Table 3 to obtain a powder composition. This powder composition was then used to fabricate a three-dimensional object using a powder sintering 3D printer (RafaelII300C-HT, manufactured by Aspect). However, the fabricated object warped and dragged, resulting in an inability to obtain a precise object.

[0139] [Table 3] [Industrial applicability]

[0140] The powder composition of the present invention contains an elastomer, and because the cooling crystallization temperature of the powder composition is low, it is possible to provide polyarylene sulfide molded products with high fracture elongation and impact strength, and no warping. [Explanation of Symbols]

[0141] 1. Tank for forming the molded object 2. Stage of the tank for forming the molded object. 3. A supply tank pre-filled with the powder composition to be supplied. 4. Stage of the tank for pre-filling with the powder composition to be supplied. 5 Recorder 6. Thermal energy 7 X, Y, Z coordinate system 8 Planar direction for stacking the powder composition 9. Height direction for stacking the powder composition 10 Three-dimensional objects P powder composition

Claims

1. A method for manufacturing a three-dimensional object, comprising supplying a powder composition for three-dimensional objects containing thermoplastic resin particles (A), wherein the thermoplastic resin composition constituting the thermoplastic resin particles (A) is a thermoplastic resin composition obtained by blending (a2) elastomer in an amount of 1 to 40 parts by weight with (a1) polyarylene sulfide resin, the D50 particle diameter of the powder composition is 10 μm to 150 μm, and the cooling crystallization temperature of the powder composition is 155°C to 220°C, to a powder bed fusion bonding type three-dimensional object manufacturing apparatus.

2. The method for producing a three-dimensional molded object according to claim 1, characterized in that the elastomer (a2) has a reactive functional group.

3. The method for manufacturing a three-dimensional object according to claim 1, characterized in that the glass transition temperature (Tg) of the elastomer (a2) is 0°C or lower.

4. The method for manufacturing a three-dimensional object according to claim 1, characterized in that the (a2) elastomer is at least one selected from the group consisting of olefin-based elastomers and silicone-based elastomers.

5. The method for manufacturing a three-dimensional object according to claim 1, characterized in that, in the morphology observed by an electron microscope, the thermoplastic resin particles (A) (a1) polyarylene sulfide resin is the matrix resin, (a2) elastomer forms island phases, and the number-mean dispersion particle diameter of the island phases is 10 μm or less.

6. A method for manufacturing a three-dimensional object according to claim 1, wherein the D90 / D10 in the particle size distribution of the powder composition is 2 or more and 10 or less.

7. The method for manufacturing a three-dimensional object according to claim 1, wherein the powder composition comprises thermoplastic resin particles (A) and resin particles (B) composed of a resin composition different from the thermoplastic resin composition constituting the thermoplastic resin particles (A), wherein the resin composition constituting the resin particles (B) includes at least one selected from the group consisting of (a1) polyarylene sulfide resin and (b) polyarylene sulfide resin different from (a1) polyarylene sulfide resin, and the cooling crystallization temperature of the resin particles (B) is 155°C or higher and 220°C or lower.

8. A method for manufacturing a three-dimensional object according to claim 7, characterized in that the total amount of thermoplastic resin particles (A) and resin particles (B) is 100 parts by weight, and the content of thermoplastic resin particles (A) is 1 part by weight or more and 100 parts by weight or less.

9. A method for manufacturing a three-dimensional object according to claim 1, characterized in that the cooling crystallization temperature of the thermoplastic resin particles (A) is 155°C or higher and 220°C or lower.

10. The method for manufacturing a three-dimensional object according to claim 1, wherein the powder composition contains 100 parts by weight of thermoplastic resin particles (A) and resin particles (B) composed of a resin composition different from the thermoplastic resin composition constituting the thermoplastic resin particles (A), and 10 to 100 parts by weight of an inorganic reinforcing material (C).

11. The method for producing a three-dimensional object according to claim 1, wherein the powder composition contains 0.1 to 10 parts by weight of inorganic fine particles (D) with a D50 particle size of 20 nm to 500 nm, with a total of 100 parts by weight of thermoplastic resin particles (A) and resin particles (B) composed of a resin composition different from the thermoplastic resin composition constituting the thermoplastic resin particles (A).

12. A method for manufacturing a three-dimensional object according to claim 1, wherein a dumbbell test specimen is prepared by powder bed fusion bonding in accordance with ISO 527-2 (2012), with its longitudinal direction parallel to the direction in which the recoater moves (X direction), and the tensile elongation at break of the test specimen in the X direction, measured according to ISO 527-2 (2012), is 1.5% or more.

13. Using a powder bed fusion bonding method, the dumbbell specimens were fabricated in accordance with ISO 527-2 (2012), with the longitudinal direction parallel to the direction of the recoater's movement (X direction). The Charpy impact strength (without notches) of a specimen cut from the parallel section of the resulting dumbbell specimen, measured according to ISO 179 (2010), was 3.5 kJ / m². 2 The method for manufacturing a three-dimensional object according to claim 1.

14. The method for manufacturing a three-dimensional object according to claim 1, characterized in that the (a2) elastomer is a thermosetting elastomer.

15. A method for producing thermoplastic resin particles (A) contained in a powder composition for three-dimensional molded objects, comprising the following steps (1) to (3). (1) A process of melt-kneading (a2) 1 to 40 parts by weight of elastomer with (a1) 100 parts by weight of polyarylene sulfide resin, and then pelletizing. (2) A step of crushing the pellets obtained in step (1). (3) A step of passing the particles crushed in step (2) through a filter with a mesh size of 45 μm or more and 250 μm or less.

16. A three-dimensional molded object manufactured by a powder bed fusion method, wherein the thermoplastic resin composition constituting the three-dimensional molded object is characterized in that, in the morphology observed by an electron microscope, (a1) a polyarylene sulfide resin is the matrix resin, and (a2) an elastomer forms an island phase, and the number-average dispersion particle diameter of the island phase is 10 μm or less.

17. The three-dimensional molded object according to claim 16, characterized in that, in the morphology observed by an electron microscope, (a1) a polyarylene sulfide resin is the matrix resin, and (a2) an elastomer forms an island phase, the number-average dispersion particle diameter of the island phase is 0.01 μm or more and 0.5 μm or less.

Citation Information

Patent Citations

  • Polyphenylene sulfide resin composition for laser welding, and composite molded product using it

    JP2005015792A

  • Powder materials (P) containing poly(arylene sulfide) (PAS) polymers and their use for additive manufacturing

    JP2022530398A

  • Powder bed fusion printing system using polyarylene sulfide powder.

    JP2023507413A

  • Resin composition, molded body, composite body and use of same

    WO2024122466A1